Structural and photoluminescence studies of erbium implanted nanocrystalline silicon thin films - Cerqueira, M. F. (2009)
Hydrogenated amorphous and nanocrystalline silicon thin films deposited by Hot Wire (HW) and Radio-Frequency Plasma-Enhanced (RF) Chemical Vapor Deposition were Er-bium-implanted. Their pre-implantation structural properties and post-implantation optical properties were studied and cor-related. After one-hour annealing at 150ºC in nitrogen atmos-phere only amorphous films showed photoluminescence (PL) activity at 1.54 μm, measured at 5 K. After further annealing at 300oC for one hour, all the samples exhibited a sharp PL peak positioned at 1.54 m, with a FWHM of ~5 nm. Amorphous films deposited by HW originated a stronger PL peak than corresponding films deposited by RF, while in na-nocrystalline films PL emission was much stronger in sam-ples deposited by RF than by HW. There was no noticeable difference in Er3+ PL activity be-tween films implanted with 1x1014 atoms/cm2 and 5x1015 at-oms/cm2 Er doses.